Organization of chromosomal DNA by SMC complexes - Yatskevich, S; Rhodes, J; Nasmyth, K (Annual Reviews, 2019)
Structural maintenance of chromosomes (SMC) complexes are key organizers of chromosome architecture in all kingdoms of life. Despite seemingly divergent functions, such as chromosome segregation, chromosome maintenance, sister chromatid cohesion, and mitotic chromosome compaction, it appears that these complexes function via highly conserved mechanisms and that they represent a novel class of DNA translocases.